2011
DOI: 10.1143/jpsj.80.043001
|View full text |Cite
|
Sign up to set email alerts
|

Haldane, Large-D, and Intermediate-DStates in anS= 2 Quantum Spin Chain with On-Site andXXZAnisotropies

Abstract: Using mainly numerical methods, we investigate the ground-state phase diagram of the S = 2 quantum spin chain described by H = j (S Quantum spin chain systems have been attracting increasing attention in recent years because they provide rich physics even when models are rather simple. The most well-known example may be the existence of the Haldane phase 1, 2) in integer spin chain systems only with isotropic nearest-neighbor (nn) interactions.In this study, using mainly numerical methods, we explore the groun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 19 publications
8
63
0
Order By: Relevance
“…A similar adiabatic connection between the S = 2 AKLT state and a trivial state is suggested recently in the analysis of finite-length S = 2 chains with both exchange and single-ion anisotropy. 40 Even if the full SU(2) invariance is maintained along the path, we have demonstrated that an even-S AKLT state is adiabatically connectable to a trivial dimerized state with broken translational symmetry.…”
Section: Discussionmentioning
confidence: 81%
“…A similar adiabatic connection between the S = 2 AKLT state and a trivial state is suggested recently in the analysis of finite-length S = 2 chains with both exchange and single-ion anisotropy. 40 Even if the full SU(2) invariance is maintained along the path, we have demonstrated that an even-S AKLT state is adiabatically connectable to a trivial dimerized state with broken translational symmetry.…”
Section: Discussionmentioning
confidence: 81%
“…[20][21][22][23][24][25][26][27] Recently, a new S = 2 linear-chain system, MnF(salen), salen = H 14 C 16 N 2 O 2 , was synthesized, and the low-field, high-temperature magnetic properties were fit with J/k B ≈ 46 K, while no evidence of a magnetic transition was detected down to 1.8 K.…”
Section: 13mentioning
confidence: 99%
“…Magnetic chains composed of spin S = 2 ions have received considerable theoretical and numerical attention [1][2][3][4][5][6][7][8] due to their unique predicted behavior. Even-and odd-integer spin chains are distinct, with the latter in a symmetry-protected topological phase [3,9].…”
Section: Introductionmentioning
confidence: 99%